2015
DOI: 10.1590/1983-21252015v28n326rc
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Productive Characterization of Forage Cactus Varieties

Abstract: -Cultivars of the genus Nopalea are known in Brazil for being tolerant to cochineal carmine attacks, thus making the cultivation of this genus a promising alternative for mitigating the negative effects of this insect on the production of biomass. With the objectives of characterizing morphologically spineless forage cactus varieties and identify morphological characteristics that may be the focus in spineless forage cactus breeding programs, an experiment was conducted in a completely randomized block design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 6 publications
1
4
0
8
Order By: Relevance
“…This fact is closely related to the growth habit of the species gender Nopalea spp., since they have open growth habit favoring the formation of areolas, or axillary buds, allowing the emergence of new cladodes, not only in cladodes apex mother as well as at their side edges (Amorim et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This fact is closely related to the growth habit of the species gender Nopalea spp., since they have open growth habit favoring the formation of areolas, or axillary buds, allowing the emergence of new cladodes, not only in cladodes apex mother as well as at their side edges (Amorim et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…cv. Miúda/Doce has increased by several factors such as resistance to pests, diseases and drought, besides being easy to manage (Amorim, Martuscello, Araújo Filho, Cunha, & Jank, 2015). However, there are few researches with varieties of the genus Nopalea.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating these results practically, it may be inferred that the cultivation of cactus genotypes that produce higher quantities of cladodes may facilitate an increase in cultivation areas, as cacti can be propagated vegetatively. In this system, plantations are filled with clones of the original plants (Amorim et al, 2015;Gebreegziabher & Tsegay, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Barbosa et al (2018) evaluated the morphological characteristics of three cactus pear genotypes (IPA Sertânia, Miúda, and Orelha de Elefante Mexicana) and found that the growth characteristics (plant height and plant width) were strongly or very strongly positively correlated with the morphological characteristics of the cladodes (basal cladode length, cladode width, cladode thickness, cladode perimeter, and cladode area), contributing to the development of the plant as a whole. Amorim, Martuscello, Araújo Filho, Cunha, and Jank (2015) evaluated the agronomic characteristics of 24 varieties of cactus pear and verified that the agronomic and morphological characteristics (plant height, plant width, cladode area, and total number of cladodes) were positively correlated with cactus pear mass.…”
Section: Introductionmentioning
confidence: 92%